“It’s not just a dream. There is a storm coming!”: Financial Crisis, Masculine Anxieties and Vulnerable Homes in American Film - Donnar, Glen (Text Matters: A Journal of Literature, Theory and Culture, 2016)
Despite the Gothic’s much-discussed resurgence in mainstream American culture, the role the late 2000s financial crisis played in sustaining this renaissance has garnered insufficient critical attention. This article finds the Gothic tradition deployed in contemporary American narrative film to explore the impact of economic crisis and threat, and especially masculine anxieties about a perceived incapacity of men and fathers to protect vulnerable families and homes. Variously invoking the American and Southern Gothics, Take Shelter (2011) and Winter’s Bone (2010) represent how the domestic-everyday was made unfamiliar, unsettling and threatening in the face of metaphorical and real (socio-)economic crisis and disorder. The films’ explicit engagement with contemporary American economic malaise and instability thus illustrates the Gothic’s continued capacity to lay bare historical and cultural moments of national crisis. Illuminating culturally persistent anxieties about the American male condition, Take Shelter and Winter’s Bone materially evoke the Gothic tradition’s ability to scrutinize otherwise unspeakable national anxieties about male capacity to protect home and family, including through a focus on economic-cultural “white Otherness.” The article further asserts the significance of prominent female assumption of the protective role, yet finds that, rather than individuating the experience of financial crisis on failed men, both films deftly declare its systemic, whole-of-society basis. In so doing, the Gothic sensibility of pervasive anxiety and dread in Take Shelter and Winter’s Bone disrupts dominant national discursive tendencies to revivify American institutions of traditional masculinity, family and home in the wakes of 9/11 and the recession.